Математичні моделі для підвищення ефективності оцінки параметрів неоднорідних середовищ за відомим розподілом розсіяного електромагнітного поля - Синявський, Андрій Тадейович (Фізико-механічний інститут ім. Г. В. Карпенка, 2016)
Дисертацію присвячено моделюванню процесів розповсюдження електромагнітних хвиль у неоднорідних середовищах з метою створення ефективних методів оцінювання параметрів цих середовищ за відомим розподілом розсіяного поля. Для розв’язання обернених задач розсіювання у випадках, що зводяться до одновимірної задачі, взаємодію електромагнітного поля з неоднорідним середовищем описано моделлю потенціального розсіювання. Розроблений підхід до оцінювання параметрів кусково-неоднорідних середовищ реалізовано через реконструкцію функції потенціалу у такій моделі та виділення особливостей цієї функції, які мають місце при розсіюванні хвиль на границях розділу середовищ. У багатовимірному випадку розвинуто наближену модель розсіювання, яка дозволила сформулювати єдину стратегію до побудови методів визначення границі контрастних розсіювачів. Розв’язання цих обернених задач полягає у встановленні індикаторної функції, що досягає максимуму в точках на поверхнях розділу середовищ. Результати числового моделювання та експерименти підтверджують ефективність запропонованих методів. Ці методи можуть бути використані у системах неруйнівного контролю для виявлення дефектів шаруватих структур, а також у системах підповерхневого та дистанційного зондування для візуалізації границі неоднорідностей. Диссертация посвящена моделированию процессов распространения электромагнитных волн в неоднородных средах с целью создания эффективных методов оценивания их параметров по известному распределению рассеянного поля. Для решения обратных задач рассеяния в одномерных случаях взаимодействие электромагнитного поля с неоднородной средой описывается моделью потенциального рассеяния. Разработанный подход к оцениванию параметров кусочно-неоднородных сред реализован путем реконструкции функции потенциала в такой модели, а также в выделении особенностей этой функции, которые имеют место при рассеянии волн на границах раздела сред. В многомерном случае предложено использовать приближенную модель рассеяния, которая позволила сформулировать общую стратегию к построению методов определения границы контрастных рассеивателей. Решение таких обратных задач состоит в построении индикаторной функции, которая стремится к максимуму в точках, принадлежащим поверхностям раздела сред. Результаты численного моделирования и эксперименты подтверждают эффективность предложенных методов. Такие методы могут использоваться в системах неразрушающего контроля для выявления дефектов слоистых структур, а также в системах подповерхностного и дистанционного зондирования для визуализации границ неоднородностей. The thesis is dedicated to simulation of electromagnetic wave propagation through inhomogeneous media in order to increase effectiveness of estimation methods of the media parameters starting from a distribution of scattered electromagnetic field, which is measured remotely. The problem arises in various branches of sciences and technology, where one needs to evaluate internal structure of objects and to estimate of their parameters by indirect methods using phenomena of electromagnetic wave scattering on inhomogeneities. Interaction of the electromagnetic field with inhomogeneous media implies a sophisticated dependency between parameters of these media and observed data, which are results of measurements. Thus the main attention in the work is paid to a question of development of electromagnetic wave scattering models, which enable to fulfill an estimation of medium parameters that is treated as an inverse scattering problem. For solving to the one-dimensional inverse scattering problems the electromagnetic wave propagation in inhomogeneous medium is described by a model of potential scattering, such as Schrödinger and Dirac’s equations. A proposed approach to estimation for piecewise-inhomogeneous medium parameters is realized by means reconstruction of a function of potential in mode of potential scattering and extrication the potential singularities, which appear for wave scattering on interfaces between media. Mathematically such a kind of problems can be reduced to Hilbert-Riemann one, which is aimed on recovery of an analytic function. Hence analysis of analytical properties of the functions is a key point in the research. One of the results of determination of analytical behavior of functions is a possibility to characterize a phase reconstruction problem, which enable to solve the inverse scattering problem uniquely for phaseless data in indentified cases. Other particular cases of application of the developed model and inverse scattering approaches include estimation of layered structures on a conducting substrate from the reflection coefficient, determination of layer parameters in a spherically symmetric radial medium starting from transmission eigen-values and estimation of parameters of a layered dielectric starting from angular dependence of the reflection coefficient. For multidimensional cases, an approximated model is proposed in order to formulate a common sampling strategy for creation of methods to determinate boundary of contrast scatterers. Solving to the inverse scattering problems consists in establishing an indicator function, which tends to maximum at sampling points that belong to an interface between media. Common principle of derivation of the methods can be described through partitioning an error of a linear estimator on two components and minimization that part, which corresponds to response of the estimator on scatterers outside a sampling point. In addition to the multidimensional inverses scattering problem, in particular cases the solution can be applied to both estimation of angles of arrival of plane waves and estimation of singularities of reflection coefficients of layered structures. An inverse scattering problem for highfrequency asymptotic is also considered as a three-dimensional surface reconstruction problem from optical cameras. Using an anisotropic diffusion model, a method is proposed to determinate a displacement field of a surface of the body, which is undergone deformations. Results of numerical simulation and experiments justify consistence of proposed models and efficiency of proposed methods. The methods can be implemented in nondestructive systems for detection of defects in layered structures as well as for subsurface sensing and remote sensing for visualization of border of inhomogeneities.
Математические модели для улучшения эффективности оценки параметров неоднородных сред по известному распределению рассеянного электромагнитного поля
Mathematical models for increase of efficacy of estimate of inhomogeneous medium parameters from known distribution of scattered electromagnetic field
Keywords: математичне моделювання; розсіювання електромагнітних хвиль; кусково-неоднорідні середовища; шаруваті структури; обернена задача розсіювання; модель потенціального розсіювання; потенціал; індикаторна функція; математическое моделирование; рассеяние электромагнитных волн; кусочно-неоднородные среды; слоистые структуры; обратная задач рассеяния; модель потенциального рассеяния; потенциал; индикаторная функция; mathematical modeling; electromagnetic wave scattering; piecewiseinhomogeneous media; layered structure; inverse scattering problem; model of potential scattering; potential; indicator function